Identifying the educational needs of physicians in pediatric epilepsy in order to improve care: results from a needs assessment in Germany, Spain, and the United States. Issue 4 (29th August 2018) - Murray, Suzanne; Labbé, Sara; Kothare, Sanjeev; Málaga, Ignacio; Kluger, Gerhard; Ogden, Patti; Lazure, Patrice; Arzimanoglou, Alexis
ABSTRACT: Aims . The objective of this study was to gather evidence‐based data on the educational needs of neuropediatricians. A needs assessment was conducted to identify the clinical challenges of physicians when diagnosing, medically treating, and managing pediatric patients with epilepsy; which could be addressed through educational interventions. Methods . A two‐phase mixed‐methods approach was used to conduct the needs assessment in Germany, Spain, and the US. Phase 1 consisted of qualitative data collection through multiple sources: a literature review, semi‐structured interviews with clinicians and nurses working in pediatric epilepsy, and interpretation and input from faculty experts. Qualitative data were coded (NVivo) and analyzed using a thematic analysis, and findings were then used to design the second phase. Phase 2 consisted of quantitative data collection through an online survey that aimed to validate the identified challenges and underlying causes using a larger sample than in Phase 1. Data from the survey were analyzed using frequency tabulations and chi‐square tests (SPSS). Results . A total of 267 participants were included in the study. Phase 1 included 88 participants (neurologists, pediatricians, neuropediatricians, and nurses). Phase 2 included 179 participants (neurologists, pediatricians, and neuropediatricians). The main areas of challenge which emerged from the triangulated data included: the integration of guidelines into practice, identification of epilepsy and epilepsy events, integration of genetic testing into practice, integration of non‐pharmacological treatments, transition from pediatric to adult care, and involvement and engagement with caregivers. Underlying causes of these challenges are reported, along with supporting qualitative findings. Conclusions . This study identified the educational needs of physicians working in pediatric epilepsy in Germany, Spain and the USA. Increasingly, educational interventions are required to be evidence‐based. The results of this study could be used to design such interventions to support neuropediatricians who wish to specialize in pediatric epileptology, in order to manage the identified challenges.